The Alchemist a magical fable about following your dream - "Coehlo, Pahlo" (Harper London, 2002)
The Alchemist is a philosophical and allegorical novel that follows the journey of a young Andalusian shepherd named Santiago. He dreams of finding a treasure located near the Egyptian pyramids and embarks on a journey that takes him across the deserts of northern Africa. Along the way, Santiago encounters various characters such as a crystal merchant, an Englishman, and an alchemist, each of whom imparts wisdom and helps him discover deeper truths about life, love, and destiny. The novel explores themes of personal legend, the pursuit of one's dreams, and the interconnectedness of all life. It is a reflection on the importance of following one's heart and recognizing the signs the universe provides to help achieve true purpose.